An investigation of the Relationship between the Audit Quality and the Cost of Equity with Sustainable Profits - Barzegarnezhad, Khosro; Jamshidinavid, Babak (International Journal of Economics and Financial Issues, 2017)
One of the items of financial statements that is considered as the evaluation criterion to performance and profitability of the profit unit is income reporting. However, calculating the net profit per unit is affected by accounting methods and estimates. Accordingly, the objective of the present research is to study the relationship between the audit quality (the audit office and the auditor tenure) and the cost of equity with sustainable profits in the companies listed on the Tehran Stock Exchange. For that, three hypotheses were formulated to address this issue and the data related to 127 member companies on the Tehran Stock Exchange were analyzed from 2010 to 2014. The regression model of the research was studied and tested through the panel data approach with fixed effects. The auditor tenure and the size of audit firm and the cost of equity are the dependent variables of research. The research method is descriptive- survey and in terms of objective and with regard to the occurrence, it is a post-incident study. The research results suggest a positive and significant relationship between the audit tenure and the audit office and the cost of equity with sustainable profits. Increasing the audit quality with regard to its impact on increasing the transparency reporting would lead to the reduction of uncertainty and information asymmetry in connection with the companies’ stock and this leads to an increase in sustainable profits. Keywords: audit tenure, audit office, cost of equity, sustainable profits JEL Classifications: C32; O13; O47